A minimal modeling framework of radiation and immune system synergy to assist radiotherapy planning. (7th February 2020) - Montaseri, Ghazal; Alfonso, Juan Carlos López; Hatzikirou, Haralampos; Meyer-Hermann, Michael
Highlights: A modeling framework to assist the decision making process in radio therapy planning. The model accounts for t umor immune system interplay and radiation induced antitumor immunity. A control engineering approach was implemented to reduce the number of model parameters. Tumor vasculature normalization combined with radiotherapy is a plausible therapeutic strategy. Time dose fractionation schemes can be determined for different tumor, immune system and treatment conditions. Abstract: Recent evidence indicates the ability of radiotherapy to induce local and systemic tumor-specific immune responses as a result of immunogenic cell death. However, fractionation regimes routinely used in clinical practice typically ignore the synergy between radiation and the immune system, and instead attempt to completely eradicate tumors by the direct lethal effect of radiation on cancer cells. This paradigm is expected to change in the near future due to the potential benefits of considering radiation-induced antitumor immunity during treatment planning. Towards this goal, we propose a minimal modeling framework based on key aspects of the tumor-immune system interplay to simulate the effects of radiation on tumors and the immunological consequences of radiotherapy. The impacts of tumor-associated vasculature and intratumoral oxygen-mediated heterogeneity on treatment outcomes are ininvestigated. The model provides estimates of the minimum radiation doses required for tumor eradication given a certain number of treatment fractions. Moreover, estimates of treatment duration for disease control given predetermined fractional radiation doses can be also obtained. Although theoretical in nature, this study motivates the development and establishment of immune-based decision-support tools in radiotherapy planning.